The Courtships of Lancaster County: Adoring Addie - Book 2 - Gould, Leslie, 1962- (Minneapolis, Minn. : Bethany House, 2013)
"Set in Lancaster County, Addie and Jonathan struggle to continue their relationship against both sets of parents' wishes. Will love finally mend the feud between their two families, or will their forbidden courtship drive everyone further apart?"--Provided by publisher.
Keywords: Amish -- Lancaster County -- Pennsylvania; Courtship -- Fiction; Man-woman relationships -- Fiction; Lancaster County (Pa.) -- Fiction; Love stories